Vida de expatriado: a narrativa de executivos brasileiros solteiros - Rosal, Anna Silvia Rosal de (2015)
The economy globalization led to increased executives expatriation. For organizations, the international transfer is limited to actions that ensure increased competitiveness and, consequently, income. For the executives, this experience transcends the professional field because it involves relational aspects in his life. The number of expatriated married executives is higher than singles. Organizations believe that family is an important factor in intercultural adaptation. In this context, the objective of this research is to understand the experiences of the process of expatriation of male, Brazilian and single executives. The researcher, therefore, resorted to the method of qualitative research with a narrative approach. The results showed that both personal and professional lives are embedded in the expatriation process. Expatriation is said to be easier for singles. However, this experience is punctuated by the ambiguity of feelings arising from events that include gains, as personal development and career improvement, while entail losses, such as the exclusion from relational network, which is strongly reported by the participants. Friendships play a significant role in the lives of singles. Specificities were identified in individual and family life cycles, as well as gender issues. The experience of expatriation covers the executive's personal, family, professional and social life aspects, and points to the need to broaden the organizations perspectives on the issue, to absorb such experience in its many facets